Perubahan Perilaku Konsumen Dalam Berbelanja Dari Ritel Tradisional Ke Ritel Modern - Helmi, Sulaiman; Syah, Lin Yan; Agustian, Wiwin (Direktorat Riset dan Pengabdian Kepada Masyarakat Universitas Bina Darma, 2019)
The problem in this study are the factors that cause changes in consumer behavior in shopping from Traditional retail to Modern Retail. Research in urban areas Palembang is a descriptive study conducted by survey method. With this method of data collected by the survey respondents in-depth interviews guidance tool of the points question. In addition to using primary data obtained from respondents also data obtained from depth interviews with informants. To develop questions, first performed exploratory study (exploratory) to potential respondents. In this study, a sample of 120 respondents represented 10 respondents from each of the East Village in District II Palembang Ilir. From the results of research obtained housewife who choose traditional retail as much as 51.7%, the dominant factor affecting consumers in the traditional retail shopping as follows: Price, Scheme & Offers, frequency of visits, and Stock Availability of Goods. From the obtained results of research conducted housewife who choose modern retailing as much as 48.3%, dominant factors that influence consumers in a retailshop at Modern as follows: Leisure Location, Convenience in Shopping, Parking Facilities, Payment Method, In the Good Customer Service, comforts for Women Workers, and Conduct, Based on the above data the researchers to conclude that in the district of East Ilir IIis not a change of behavior in the selection of retail shopping from traditional to modern retail.